Jutta and Hildegard: the Biographical Sources - Silvas, Anna (Brepols, 1998)
This book is a comprehensive collection of biographical sources, all translated from the latest critical editions, relating to Jutta of Disibodenberg (1092-1136) and Hildegard of Bingen (1098-1179). Except for the Life of Hildegard they have never been translated before. The Life of Jutta in particular is a major source recently discovered, throwing new light on the early life of Hildegard. The contents include translations with scholarly introductions of the following documents: The Chronicles of Disibodenberg (selections); Charters of Disibodenberg; Documents of Sponheim; The Life of Jutta; Guibert's Letter 38 to Bovo (including his incomplete Life of Hildegard); the Life of Hildegard; Eight Readings to be read on the Feast of St Hildegard; Guibert's Revision of the Life of Hildegard; Charters of Rupertsberg; Canonisation Proceedings.